Encoding Memory through Multimodality in Modern-Day Memorial Museums: Concerns over the Use and Possible Overuse of Technology. The Example of the Armenian Genocide Museum-Institute - Ghazaryan, Grigor; Donatelle, Steven (HERMES - Journal of Language and Communication in Business, 2022)
The article is devoted to the study of the use of technology in memorial museums, particularly in those related to geno-cide, with a goal to construct a theoretical framework that can be used to reflect on and analyze the use of technology in similar spaces. A multidisciplinary theoretical framework is assembled through Semiotics, Communication and Memory Studies, as well as Philosophy, in order to explain the benefits and dangers of implementing technology in memorial museums. Particularly, Peirce’s idea ofunlimited semiosis, Eco’s considerations about the multiplicity of meanings (“open text”), the existence of two narratives in memorial museums, Heidegger’s writings on technology (especially enframing and revealing) and Jakobson’s communication theory based on Buhler’s organon model are invoked with the aim of explicating the interplay between technology and memory. Proceeding inductively from the example of the Arme-nian Genocide Museum Institute (AGMI), the authors identify general dangers that should be kept in mind in the process of genocide memorialization.